2021
DOI: 10.3389/fevo.2021.609627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Use History on Biodiversity of Pine Plantations

Abstract: The growing replacement of native vegetation by forest plantations is considered a global threat to biodiversity. Significant variation in biotic communities among stands with similar management suggests that previous land use might have an effect on the capacity of forest plantations to harbor native species. The goal of our study was to determine the effect of land-use history on the biodiversity currently present in pine plantations in the coastal range of Central Chile. In particular, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 132 publications
(155 reference statements)
2
4
0
4
Order By: Relevance
“…These results have been translated into landscape homogenization dynamics, which can be seen in the increase in the number of patches and the decrease in their size. This had already been reported for southern central Chile [12,73].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results have been translated into landscape homogenization dynamics, which can be seen in the increase in the number of patches and the decrease in their size. This had already been reported for southern central Chile [12,73].…”
Section: Discussionsupporting
confidence: 74%
“…At the beginning of the forestry model in 1974, the native forest occupied soils of greater accessibility in the intermediate depression and on the eastern slope of the coastal range between Maule (34 • LS-71 • W) and Araucanía (39 • LS-72 • W) [73]. However, the substitution of native forest by exotic plantations is not complete because this mountain range still has relics of native vegetation with high ecological value.…”
Section: Discussionmentioning
confidence: 99%
“…of land use intensification has been reported for beetles and other insects in tropical forests in Asia, as well as in Africa and America(Phillips et al, 2017). Several observational and experimental studies have revealed that the conversion of natural forests into plantations is harmful to species that cannot adapt to their new environmental conditions(Uribe et al, 2021;Warren-Thomas et al, 2015); our results show that Laos is no exception. Therefore, a large number of insect communities may be, currently or in the near future, at risk from land use intensification in Laos, even though the region is still mainly covered by mountains and forests.A more in-depth understanding of the response of beetle diversity to current and future economic development in Laos is needed to implement practical conservation actions.…”
supporting
confidence: 54%
“…Un factor recurrente en la evaluación de la homogeneización es el cambio en el uso y la cobertura de la tierra, pero solo una publicación lo evaluó a lo largo del tiempo. Uribe et al (2021) estudiaron la influencia de este factor en la biodiversidad en plantaciones de Pinus, donde la escala temporal estuvo representada por el tiempo de rotación de cada plantación (20 años). Se encontró que las plantaciones que reemplazaron directamente a los bosques nativos presentaban un gran número de especies especialistas y un menor número de generalistas, y que el número de rotaciones no influía en la diversidad local.…”
Section: Caracterizaciónunclassified